Simple soft chemical synthesis and characterization of phase pure co-doped LiMn2O4 nanoparticles as cathode materials for Li-ion battery applications - S. Nesaraj, Arputharaj; S. Deepi, Alagu; Srikesh, Gopalakrishnan (Asia-Pacific Journal of Science and Technology, 2021)
Spinel LiMn2O4 is considered as a best cathode material for Li-battery applications. Lithium ion battery has high energy density and long service life and hence it is used in portable electronic devices and electric vehicles. In this research work, a series of Co-doped LiMn2O4 nanoparticles, viz. LiMn2-xCoxO4-δ (where x = 0, 0.1, 0.2, 0.3, 0.4 and 0.5) were prepared by a simple one-pot combustion synthetic route with urea as an organic fuel. The prepared materials were characterized by X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), particle size analysis, Scanning Electron Microscope (SEM) and Energy Dispersive X-ray (EDAX) analysis. The electrochemical properties of the prepared materials were studied by AC impedance analysis. The result indicates that doping of Co in LiMn2O4 can improve the electrical characteristics of the spinel. It was found that LiMn1.5Co0.5O4-δ sintered specimen has shown better conductivity value of 1.45 x 10-5 Scm-1 among all other samples studied. Based on the results, we propose that Co-doped LiMn2O4 spinel can be an attractive cathode material for Li-ion battery applications.